The Surface Hardness Measurement of Stone and Improved Die Stone After the Addition of a Mixture of Chemical Additives with Different Proportion - Al Hadad, Anaam Sh.; Al Huwaizi, Abbas F; Al Huwaizi, Raed F (Journal of Baghdad College of Dentistry, 2018)
Background: Incorporation of chemical additives has long been a technique used to improve properties of the gypsum products. The purpose of this work was to study the effects of adding a combination of gum Arabic and calcium hydroxide to a type III dental stone and type IV improved die stone with different proportion. The effect on water/powder ratio, and surface hardness was determined. Material and method: Both material stone and die stone were blended with two proportion of additives so that each material was mixed twice but with different proportion of gum Arabic (0.1% and 0.2%) and calcium hydroxide (0.5 % and 0.3%). Data for hardness were subjected to two-way analysis of variance. Results: The results revealed that the chemical additives were reduced the water requirements of gypsum products so that the reduction of water lead to increase the density of mixture that sets harder. For type III dental stone the additives significantly improved the surface hardness, while for type IV improved die stone the surface hardness was not enhanced except it was designed to be mixed at low water/powder ratio, and in some instances a reduction in hardness was observed, especially at the most reduced water / powder ratio (0.18).